State Plan Proposals 1986-87 Volume I Government of West Bengal - Planning Commission (Planning Commission, 1985)
Despite a severe crunch of resources because of the non-implementation of the recommendations of the 8th Finance Commission during 1984-85 - the last year of the Sixth Plan, when some Rs. 325 crores of Central assistance were denied to the State, in terms of physical achievements, the Sixth Plan ended in an optimistic note for the State. Not only was a record production of 92.57 lakh tonnes of food-grains achieved in the terminal year of the Sixth Plan, significant progress was attained in many sectors of the State's economy.
Government of West Bengal, Development and Planning Department